2009
DOI: 10.4049/jimmunol.0902773
|View full text |Cite
|
Sign up to set email alerts
|

CD8 T Cell-Initiated Vascular Endothelial Growth Factor Expression Promotes Central Nervous System Vascular Permeability under Neuroinflammatory Conditions

Abstract: Dysregulation of the blood-brain barrier (BBB) is a hallmark feature of numerous neurologic disorders as diverse as multiple sclerosis, stroke, epilepsy, viral hemorrhagic fevers, cerebral malaria, and acute hemorrhagic leukoencephalitis. CD8 T cells are one immune cell type that have been implicated in promoting vascular permeability in these conditions. Our laboratory has created a murine model of CD8 T cell-mediated CNS vascular permeability using a variation of the Theiler’s murine encephalomyelitis virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 70 publications
4
81
0
Order By: Relevance
“…Through analysis of FITC-albumin leakage into the brain, it was found that inhibition of neuropilin-1 with high doses of ATWLPPR VEGF inhibitor resulted in decreased CNS vascular permeability when compared to mice treated with PBS or scrambled RAPTLWP peptide. Furthermore, there was no significant difference between mice treated with VEGF inhibitor and mice treated with mock E7 peptide (Suidan et al, 2010). As previously reported using the PIFS model, degradation of the tight junction protein occludin occurs prior to CNS vascular permeability .…”
Section: Inducible Model Of Severe Vascular Permeability: Peptide-indsupporting
confidence: 55%
“…Through analysis of FITC-albumin leakage into the brain, it was found that inhibition of neuropilin-1 with high doses of ATWLPPR VEGF inhibitor resulted in decreased CNS vascular permeability when compared to mice treated with PBS or scrambled RAPTLWP peptide. Furthermore, there was no significant difference between mice treated with VEGF inhibitor and mice treated with mock E7 peptide (Suidan et al, 2010). As previously reported using the PIFS model, degradation of the tight junction protein occludin occurs prior to CNS vascular permeability .…”
Section: Inducible Model Of Severe Vascular Permeability: Peptide-indsupporting
confidence: 55%
“…The effects of VEGF in gliomas have been shown to be enhanced by hypoxia, tumor cell expression of the cytokine, and hematopoietic derived factors [4,5,57]. More recently, CD8+ and CD4+ T cells have been demonstrated to promote VEGF upregulation in the CNS under neuroinflammatory conditions [35,36]. While enhanced VEGF expression in our model is apparent, the source of this increase requires further investigation.…”
Section: Discussionmentioning
confidence: 68%
“…Additionally, detailed characterizations of the effector functions of infiltrating immune cells, including alterations to cytotoxic function and immunosuppressive capacity, are underway. Furthermore, reciprocal studies will investigate altered angiogenic responses following enhancement of antitumor responses, as immune cells have also been shown to modulate VEGF expression and angiogenesis [35,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Splenocytes were stained for the expression of cell surface TGF-␤RII and viral Ag-tetramers and analyzed by flow cytometry. D b :VP2121-130 and D b :GARC tetramers were made as previously described (19). In additional experiments, splenocytes were stimulated in vitro with viral peptides or control antigen and analyzed for the expression of IFN-␥ by intracellular staining among viral-specific CD8 ϩ T cells.…”
Section: Murine Cd8mentioning
confidence: 99%